Preparing and delivering scientific presentations a complete guide for international medical scientists - Giba, John.; Ribes, Ramón; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
The latest in Springer's "Medical English" series aimed at healthcare professionals who need English for their work but do not speak English on a day-to-day basis, this book features clear advice on a variety of topics relevant to the successful preparation and delivery of scientific presentations. It also covers a wide range of situations that may develop in the context of an international congress and includes specific chapters on important issues like dealing with questions, chairing sessions, and avoiding common pitfalls in English usage and pronunciation. Although much of the information provided will be useful for scientists of all backgrounds and nationalities, the book is aimed especially at non-native English-speaking physicians and biomedical scientists. It will be an invaluable addition to the libraries of experienced presenters as well as of those just beginning their careers in international science.
To Speak or Not to Speak? Questions You Should Ask Yourself before Agreeing to Do a Talk in English -- Preparing a Talk -- Useful Language for Scientific Presentations -- Common Mistakes in Language Usage -- Delivering a Talk -- The Dreaded Questions and Comments Section -- Chairing a Session -- Attending an International Scientific Congress -- Conversation Survival Guide -- Improving Your Pronunciation -- Appendices.
Electronic reproduction.
Keywords: English language -- Conversation and phrase books (for medical personnel); English language -- Medical English; Public speaking; Medical illustration; Medical writing; Electronic books